(untitled) (Central Medical College Journal, 2023)
Background: Snake bite is one of the leading causes of mortality and morbidity in many regions, notably the rural tropics, and is a globally overlooked occurrence. Present study is aimed to find the pattern and seasonal variations of snakebite in the southern part of Bangladesh. Methods: A one-year retrospective survey was done on 554 venomous or non-venomous snake bite patients admitting in a tertiary care hospital Chittagong Medical College Hospital, Bangladesh. Through the administration of a questionnaire, data on snake bites and kinds, date and time of bite and envenomation characteristics were obtained from respondents over a twelve-month period. After data collection, SPSS-20 was utilized for analysis. Results: In the present study male (64.1%) were found more affected than female and the vast majority of snake bite victims are younger Regarding pattern of envenomation, 400(72.2%) patients had no features of envenomation, 37(6.7%) local envenomation with spontaneous bleeding, 35(6.3%) had systemic envenomation, 74(13.4%) had local envenomation and 8(1.4%) had local swelling with neurotoxicity. Most of the patients were male (64.1%), female was mostly housewives (24.9%) and 68.1% were from poor socioeconomic status. Regarding monthly distribution of study patients where most patients were found during May to September and venomous bite were also more common during the month of May to August. Analysis of species of snakes revealed 89(16.1%) were pit viper, 87(15.7%) were dora snake, 23(4.2%) were cobra and 355(64.1%) snake bite were remained unidentified. Conclusions: During the monsoon season (May to September) in Bangladesh, the incidence of both nonvenomous and venomous snake bites is much high and poisonous snake bites are prevalent during this time. Poor access to health services and superstition regarding dealing with Ozahs are also a common finding in our study. Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 71-76